PERAN KONTROL KOGNITIF DALAM KEMAMPUAN WORD RETRIEVAL PADA ANAK GANGGUAN BAHASA PERKEMBANGAN DI RSPAL DR. RAMELAN SURABAYA : THE ROLE OF COGNITIVE CONTROL IN WORD RETRIEVAL ABILITY IN CHILDREN WITH DEVELOPMENTAL LANGUAGE DISORDERS AT RSPAL DR. RAMELAN SURABAYA - Adha; Siswanto, Arif; Gunawan (JURNAL TERAS KESEHATAN, 2025)
Language disorders are problems in the areas of language form, language content and language use that are common in children. Children with developmental language disorders have difficulty in accessing and processing appropriate vocabulary, which affects their word retrieval skills. Word retrieval ability is influenced by linguistic factors but this ability can also be influenced by children's cognitive abilities. This study aims to determine the distribution of the role of cognitive control in word retrieval ability in children with developmental language disorders aged 4-6 years at RSPAL dr. Ramelan Surabaya. This quantitative research was conducted with a correlative test and with a cross-sectional approach to analyze the cause-and-effect relationship between the two variables. The number of samples used in this study was 35 children using total sampling data collection techniques. Data were analyzed using univariate analysis and bivariate analysis using the Kendall Tau test.